Education on the Use of Herbal Plants for Women's Reproductive Health at the Rumah Herbal Mirasa UMKM - Anggariyanti, Sinta (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Background: Reproductive health in women of childbearing age is very important and requires special attention. Various kinds of problems during a woman's fertile period can have a serious impact on women's health. Women's reproductive health problems that often arise and disrupt women's quality of life can be seen from the prevalence of cervical cancer and breast cancer in Indonesia. Maternal reproductive problems apart from having a physical impact, can also affect mental and emotional health, economic conditions and social welfare in the long term. Method: Implementation of community service in the form of education in the form of lectures and discussions about the use of herbal plants for women's reproductive health and carried out for one day. Conclusion: Community service activities with the theme "Education on the use of herbal plants for women's reproductive health at Rumah Herbal Mirasa UMKM" can increase knowledge about the benefits of herbal plants for women's reproductive health as an effort to prevent reproductive problems in women of childbearing age.